Comparative characteristics structure physically prepared fighters high qualification light, medium and heavy weight category - Pryimakov, O.O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : study of the structure of physical preparedness (PP) highly skilled fighters of different weight categories. Material : 147 athletes surveyed in separate weight classes. Recorded 26 indicators PP. Results : It was found that the mass of fighters is an important determinant of the level of development, value and structure of the phase relationship indicators. Informative indices PP interrelated with weight category fighters are: Runtime 45 shots in a specialized test, the number of pull-ups in the maximum rate of 10 seconds and the maximum number is not limited to a run-time while climbing a rope to a height of 4 m, height of jumps up to space. With the increase in the weight category of fighters dropping speed, relative strength, speed and power endurance, reduced muscle explosive quality, the level of special performance. Same relationship PP indicators reflecting its structure changed insignificantly. Conclusions : The developed regression models should be used for modeling and prediction of individual athletes sides PP light, medium and heavy weight categories, construction of group regulatory assessment scales.